4 - Transcultural Memory in Post-Conflict Northern Uganda War Commemorations: David Mwambari - Mwambari, David (Africa Development, 2021)
This article draws from debates on the transcultural turn in memory studies, exploring the multiple ways in which memory unfolds in post-war contexts and across cultures. Using interviews, ethnography and secondary sources, it builds on research critical of how specific post-war experiences in African societies are framed and subsumed into global memory practices and transmission, particularly in the global North. The article finds that, while on the surface memorials and rituals appear to be influenced by Euro-American-centric memory transmission practices, a deeper examination of commemorations in Northern Uganda reveals that processes of commemorating the past are complex and multi-layered. It argues that indigenous gatekeepers and keepers of memory are engaged in a dynamic process of creating something new out of the ruins of the past (Mbembe 2020). Local contexts allow for the examination of nuanced experiences and practices that should also be part of the knowledge of universal experience, leading us to rethink the relationship between what are referred to as universal models of remembering and their appropriation at the local level. This study proposes thinking differently about what constitutes this hybridity, especially local actors’ strategic use of their available resources to meet their memorialisation needs and to find meaning in mnemonic rituals and spaces, in post-conflict countries.